2016
DOI: 10.1038/srep37164
|View full text |Cite
|
Sign up to set email alerts
|

Forms and Lability of Phosphorus in Algae and Aquatic Macrophytes Characterized by Solution 31P NMR Coupled with Enzymatic Hydrolysis

Abstract: Solution Phosphorus-31 nuclear magnetic resonance (31P NMR) spectroscopy coupled with enzymatic hydrolysis (EH) with commercially available phosphatases was used to characterize phosphorus (P) compounds in extracts of the dominant aquatic macrophytes and algae in a eutrophic lake. Total extractable organic P (Po) concentrations ranged from 504 to 1643 mg kg−1 and 2318 to 8395 mg kg−1 for aquatic macrophytes and algae, respectively. Using 31P NMR spectroscopy, 11 Po species were detected in the mono- and dieste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…The mean ratio of P o /TP of the six algal samples was 69.2% in Chao Lake (Table 1). This value was greater than that of algae from Tai Lake (mean ratio of P o /TP 57.8%) (Feng et al 2016b). The previous studies reported that P o could be converted to bioavailable P (e.g., HPO 4 2− ) for algae blooming through a series of redox-driven solubilization reactions and phosphatase-mediated hydrolytic processes (Wang and Pant 2010;Zhu et al 2015).…”
Section: Nutrients (C N and P) In Debris Of Algaementioning
confidence: 75%
See 4 more Smart Citations
“…The mean ratio of P o /TP of the six algal samples was 69.2% in Chao Lake (Table 1). This value was greater than that of algae from Tai Lake (mean ratio of P o /TP 57.8%) (Feng et al 2016b). The previous studies reported that P o could be converted to bioavailable P (e.g., HPO 4 2− ) for algae blooming through a series of redox-driven solubilization reactions and phosphatase-mediated hydrolytic processes (Wang and Pant 2010;Zhu et al 2015).…”
Section: Nutrients (C N and P) In Debris Of Algaementioning
confidence: 75%
“…Samples of algae were extracted by use of optimized NaOH-EDTA extracting agent (mixtures of 0.5 mol l −1 NaOH and 25 mmol l −1 EDTA) with a ratio of 150:1 (ml g −1 ), and the mixtures were shaken for 18 h at room temperature (Cade-Menun and Preston 1996;Feng et al 2016b). The extracting solutions were centrifuged (8000 × g) for 30 min, and filtered through 0.45-μm glassfiber filters (Whatman GF/C).…”
Section: Extraction Of P and Chemical Analysismentioning
confidence: 99%
See 3 more Smart Citations